Application of Interferometric MASW to a 3D-3C Seismic Survey. Issue 1 (1st December 2016) - Strong, Shaun; Hearn, Steve
Abstract : Multichannel analysis of seismic surface waves (MASW) is well developed for shallow geotechnical applications. The technique has received much less attention in 3D reflection. The primary goal of this investigation is to develop an improved methodology for extracting S-wave receiver statics in 3D converted-wave (PS) reflection surveys. The main challenge of using MASW in this context is the increased receiver spacing. To overcome this we need to include multiple sources in each dispersion analysis. Unfortunately, adding more sources increases the chance that the dispersion image will be degraded due to lateral near-surface variations. We present a methodology which incorporates interferometry into the MASW method (IMASW). This effectively repositions sources at receiver locations, reducing the region over which lateral variations can contribute to the data. Application of this approach to a 3D-3C trial dataset provides an alternate approach for determining the S-wave receiver statics solution for converted-wave reflection surveys.